Diversity and Distribution of Anaerobic Ammonium Oxidation Bacteria in Hot Springs of Conghua, China - Liu, Lan; Lv, Ai-Ping; Narsing Rao, Manik Prabhu; Ming, Yu-Zhen; Salam, Nimaichand; Li, Meng-Meng; Liu, Ze-Tao; Zhang, Xiao-Tong; Zhang, Jing-Yi; Xian, Wen-Dong; Jiao, Jian-Yu; Li, Wen-Jun (Frontiers in Microbiology, 2022)
Anaerobic ammonium oxidation (anammox) is an important process of the nitrogen cycle, and the anammox bacteria have been studied in a wide variety of environments. However, the distribution, diversity, and abundance of anammox bacteria in hot springs remain enigmatic. In this study, the anammox process was firstly investigated in hot springs of Conghua, China. Anammox-like bacterial sequences that closely affiliated to ‘Candidatus Brocadia’, ‘Candidatus Kuenenia’, ‘Candidatus Scalindua’, ‘Candidatus Anammoxoglobus’ and ‘Candidatus Jettenia’ were detected. Several operational taxonomic units (OTUs) from this study shared low sequence identities to the 16S rRNA gene of the known anammox bacteria suggesting that they might be representing putative novel anammox bacteria. Quantitative PCR analysis of anammox-specific 16S rRNA gene confirmed that the abundance of anammox bacteria ranged from 1.60×104 to 1.20×107 copies L-1. Nitrate was a key environmental factor defining the geographical distribution of the anammox bacterial community in the hot spring ecosystem. Dissolved inorganic carbon had a significant influence on anammox bacterial biodiversity. Our findings for the first time revealed that the diverse anammox bacteria, including putative novel anammox bacterial candidates, were present in Conghua hot spring, which extended the existence of anammox bacteria to the hot springs in China and expands our knowledge of the biogeography of anammox bacteria. This work filled up the research lacuna of anammox bacteria in Chinese hot spring habitat, and would guide for enrichment strategies of anammox bacteria of Conghua hot springs.